Acetyl-L-carnitine：An Effective Antioxidant against Cryo-damage on Human Spermatozoa with Asthenospermia - 邹宇洁;杨菁;常硕;徐望明;尹太郎;龙文 (Current medical science, 2017)
A variety of natural and artificial cryoprotectant extenders have been explored to enhance sperm recovery following cryopreservation-thawing process. The current investigation is aimed at evaluating the effect of acetyl-L-carnitine on human spermatozoa and reactive species oxygen（ROS） level after freezing-thawing process. The spermatozoa were collected from 35 male patients diagnosed as having asthenospermia. The cryopreservation of human spermatozoa treated with acetyl-L-carnitine at different concentrations（group B： 2.5 mmol/L, group C： 7.5 mmol/L, group D： 15 mmol/L） was compared with control（group A： no acetyl-L-carnitine given）. For the frozen-thawed spermatozoa, the viability, motility and DNA integrity were measured by comet assay, acrosome integrity by FITC-PNA staining and ROS level was determined in each group. The results showed that there were no significant differences in motility and viability between group A and group B, while the motility and viability of spermatozoa in group C and group D were significantly increased as compared with those in group A. As compared with group A, the values for DNA integrity parameters including comet rate（CR）, tail DNA percentage（TD）, tail length（TL） and Oliver tail moment（OTM） were significantly reduced in group C and group D. Group C and group D also displayed a higher proportion of intact acrosome than group A. No significant difference in ROS level was found between group A and group B, while with the increase in acetyl-L-carnitine concentration, the ROS level in groups C and D was significantly reduced as compared with that in group A. In conclusion, acetyl-L-carnitine at a concentration of 7.5 mmol/L is an effective antioxidant against cryo-damage on post-thawed human spermatozoa.